(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Kidney transplant recipients are at risk of opportunisticinfections; previous studies demonstrated the association betweenlow level of vitamin D and the risk of viral infections. This studywas designed to evaluate the relationship between serum 25-hydroxyvitamin D level and active Cytomegalovirus infection / disease inkidney transplant recipients.Methods. A total number of 83 kidney transplant recipients enrolledin this case-control study from June 2013 to January 2014. 38patients had active CMV infection / disease and 45 patients hadno evidence of active CMV infection. Serum level of 25-hydroxyvitamin D was measured in these two groups and classified asdifferent levels of sufficient (more than 30ng/mL), insufficient (15-30ng/mL), and deficient (less than 15 ng/mL). Data were analyzedin SPSS 21 statistical software by using statistical tests of Pearsoncorrelation coefficient, chi-square and t-test.Results. Mean serum 25-hydroxy vitamin D level was 14.42 ng/mL in case group and 17.52 ng/mL in control group. There wasno significant difference between the groups in terms of patients’characteristics (P > .05). No significant statistical difference wasfound between mean 25-hydroxy vitamin D level in case and controlgroups (P > .05) but Vitamin D deficiency (serum 25-hydroxy vitaminD less than 15 ng/mL) was noticed in 63.1% of CMV infected groupversus 42.2% of control group. Thus vitamin D deficiency was seenmore prevalent in the CMV infected group (P > .05).Conclusion. Although we did not find a statistically significantrelationship between vitamin D levels and the CMV infection, CMVinfected patients had lower vitamin D level compared with noninfectedrecipients, hence vitamin D deficiency can be consideredas a risk factor for CMV reactivation after renal transplantation.